Asymptomatic Leishmania Infected Children: A Seroprevalence and Molecular Survey in a Rural Area of Fars Province, Southern Iran - Akram Layegh Gigloo; Bahador Sarkari; Zahra Rezaei; Gholam Reza Hatam; Mohammad Hassan Davami (Journal of Tropical Medicine)
The current study aimed to evaluate the seroprevalence of visceral leishmaniasis in asymptomatic healthy children in a rural area of Fars province, Southern Iran. Blood samples were taken from 617 asymptomatic healthy children and serum samples along with buffy coat were separated from the blood. The serum samples were assessed for antibodies against Leishmania infantum by an indirect ELISA and the buffy coats were tested for the presence of L. infantum DNA by molecular method. Of the 617 recruited children, 297 (48.1%) were female and 317 (51.4%) were male. Anti-Leishmania antibodies were detected in 17 (2.8%) of the children. From those 17 seropositive cases, 5 (29.4%) were male and 12 (70.6%) cases were female. Children aged 5–8 years had the highest seroprevalence rate; however, no associations were found between seropositivity to Leishmania and gender or age of the children. Moreover, L. infantum DNA was detected in buffy coat of 8 (1.3%) of 617 children. Three of the PCR-positive cases were seropositive whereas 14 of seropositive subjects (82.3%) were PCR-negative. Findings of the current study revealed a considerable subclinical leishmanial infection in children in the studied rural area in the south of Iran. Results of the current study could be used for surveillance, prevention, and control of VL in the area.